Analysis of the Role Teachers in Implementation Merdeka Curriculum in Primary School - Ahmad Yudi Saputra; Faizi Anwar; Deny Susanti; Baiq Rizki Hidayati; M. Al Fadhil (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This research aims for examine further​ the role of teachers in implementation curriculum Independence at State Elementary School 5 Selong as well as identify factor barriers faced by teachers in implementation curriculum This type of research uses study qualitative with method phenomenology for understand teacher experience in implement curriculum This, with focus on challenge empowerment digital technology. Research results show that implementation The Merdeka Curriculum is not yet evenly distributed across all classes, and there are limitation’s ability digital technology becomes challenge main for teachers in its implementation. Teachers play a very important role as facilitators, guides, and innovators. as well as own a very significant role in implementation Merdeka Curriculum, which demands ability in teaching according to development student as well as contribution through the Merdeka Belajar platform. Observation shows that not yet all classes implement Curriculum Independent in effective, and some teachers, especially older ones, experience difficulty in utilise digital technology that supports curriculum said. Achievement or result of implementation from the Role of Teachers in Implementation Merdeka Curriculum in implementing P5.